The effect of music and movie-watching on hemodynamic parameters of patients undergoing extracorporeal lithotripsy - Mostafa Roshanzadeh; Majid Shirani; Ali Tajabadi; Mina Shirvani; Somayeh Mohammadi (Tehran University of Medical Sciences, 2021)
Background & Aim: Changes in hemodynamic parameters can indicate the health status of individuals, and treatment measures cause changes in hemodynamic parameters, and affect the treatment process of patients. Different ways of distraction can have different effects. The aim of this study was to determine the effect of music distraction and movie-watching on hemodynamic parameters of patients undergoing extracorporeal lithotripsy. Methods & Materials: A quasi-experimental study with a three-group, before and after design was performed on 90 patients undergoing extracorporeal lithotripsy in the lithotripsy unit of Ayatollah Kashani hospital affiliated to Shahrekord University of Medical Sciences in 2018. Patients were selected using the convenience sampling method and randomly allocated into three groups. The intervention included visual and auditory distraction. Data was collected before and after the intervention using demographic characteristics questionnaire, calibrated mercury blood pressure monitor, and pulse oximeter. Descriptive statistical tests (mean and standard deviation, percentage, frequency) and inferential tests (paired t-test, Pearson correlation coefficient and analysis of variance) through the SPSS software version 16 were used to analyze the data. Results: Analysis of variance showed that the mean scores of systolic and diastolic blood pressure, pulse rate and oxygen saturation in the auditory, visual and control groups were not significantly different before the intervention (P>0.05). Also, the mean scores of these variables in auditory, visual and control groups were not significantly different after the intervention (P>0.05). Paired t-test also showed the mean scores of pulse rate (P=0.133), systolic (P=0.159) and diastolic blood pressure (P=0.413), and oxygen saturation (P=0.083) did not have significant differences after the intervention compared to before the intervention between the groups. Conclusion: According to the results, music and movie-watching did not have a significant effect on hemodynamic parameters of patients undergoing lithotripsy. Due to the lack of confirmatory studies, further research is needed on lithotripsy patients.